2007
DOI: 10.1021/la0633841
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Nitric Oxide-Releasing Gold Nanoparticles

Abstract: The synthesis and characterization of water-soluble nitric oxide (NO)-releasing monolayer-protected gold clusters (MPCs) are reported. Tiopronin-protected MPCs ( approximately 3 nm) were functionalized with amine ligands and subsequently exposed to 5 atm of NO to form diazeniumdiolate NO donors covalently bound to the gold MPC. Diazeniumdiolate formation conditions, NO-release, and nanoparticle stability were examined as a function of the structure of the protecting ligand, pH, and storage time. Despite their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 33 publications
1
105
1
1
Order By: Relevance
“…For our surprise, this procedure reduced the NO release. These results are different of the results obtained by Polizzi et al [15]. In accordance to our finding, Rothrock et al [14] reported that at 37°C the NO donor coupled to AuNPs released low levels of NO.…”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…For our surprise, this procedure reduced the NO release. These results are different of the results obtained by Polizzi et al [15]. In accordance to our finding, Rothrock et al [14] reported that at 37°C the NO donor coupled to AuNPs released low levels of NO.…”
Section: Resultscontrasting
confidence: 85%
“…Rothrock et al [14] reported the synthesis of gold nanoparticles that was designed to control the NO release. A few years later, Polizzi et al [15] reported the synthesis of water-soluble NO-releasing gold nanoparticles with significantly enhanced NO payloads.…”
Section: Introductionmentioning
confidence: 99%
“…Schoenfisch et al have likewise shown that nitric oxide (NO) can be efficiently released at acidic pH from gold nanoparticles. [103] Besides the surface chemistry of nanoparticles, the unique physical properties of nanoparticles have been utilized in the design of DDSs. Ford et al have designed a water-soluble nanocontainer for NO storage based on electrostatic assembly of DHLA-coated quantum dots and cationic dinitro complexes that uses energy transfer from the core to release NO.…”
Section: Nanoparticles As Drug Delivery Systemsmentioning
confidence: 99%
“…In another study done by the same research group, water-soluble NO-releasing AuNPs were synthesized from Tiopronin-protected MPCs (Tio-MPCs) via similar modifications. [89] Despite the water solubility, the NO-releasing Tio-MPCs could only release modest amount of NO (<0.023 µM/mg) for short durations (<1.5 h). In the same study, they also demonstrated that the NO storage capacity and release stability could be improved by using polyamine-stabilized MPCs, which could release 0.386 µM/ mg NO within up to 16 h after modifications.…”
Section: Gold Nanoparticles (Aunps)mentioning
confidence: 98%